Fracture of rotary nickel titanium instruments - Rajendra Kumar Tewari; Bhumika Kapoor; Ashok Kumar; Surendra Kumar Mishra; Syed Mukhtar- (Wolters Kluwer Medknow Publications, 2017)
With the advent of rotary nickel titanium (NiTi) instruments, preparation of curved canals have become easy but chances of instrument separation have increased. Such an instrument separation can cause procedural problems in rendering endodontic therapy. There are various factors that cause separation of rotary NiTi instruments. These factors, various failure mechanisms and impact on the prognosis of instrument separation have to be well understood by the clinician.